2016
DOI: 10.1097/md.0000000000003096
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits Are Associated With School Performance in Adolescents

Abstract: Several studies suggest that dietary habits are associated with poor academic performance. However, few studies have evaluated these relations after adjusting for numerous confounding factors. This study evaluated the frequency of various diet items (fruit, soft drinks, fast foods, instant noodles, confections, vegetables, and milk) and the regularity of meal times (breakfast, lunch, and dinner) all at once.A total of 359,264 participants aged from 12 to 18 years old were pooled from the Korea Youth Risk Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 41 publications
9
81
1
4
Order By: Relevance
“…Supporting to these study findings, [40] ; [46]; [58] and [59], revealed that meal leaving out; principally breakfast, and diverse weight loss eating behaviors were various unhealthy dietary behaviors showed by Malaysian adolescent girls. This in line with [47], who reported that less than half of study subjects had breakfast daily.…”
Section: The Association Between Eating Habits and Body Mass Index Amsupporting
confidence: 60%
“…Supporting to these study findings, [40] ; [46]; [58] and [59], revealed that meal leaving out; principally breakfast, and diverse weight loss eating behaviors were various unhealthy dietary behaviors showed by Malaysian adolescent girls. This in line with [47], who reported that less than half of study subjects had breakfast daily.…”
Section: The Association Between Eating Habits and Body Mass Index Amsupporting
confidence: 60%
“…This prevalence is much lower once compared with Egyptian adolescent athletes (78.5%) (33). Eating breakfast regularly is relevant, as it reduces the consumption of unhealthy snack foods during the day and may improve consumption of fiber-rich products and lead to a more even distribution of energy and nutrient intake throughout the day, that may improve glucose and insulin metabolism, appetite regulation (hunger and satiety); thus reducing risk of becoming overweight (5). Moreover, breakfast consumption may improve cognitive function and school performance (5).…”
Section: Discussionmentioning
confidence: 99%
“…Eating breakfast regularly is relevant, as it reduces the consumption of unhealthy snack foods during the day and may improve consumption of fiber-rich products and lead to a more even distribution of energy and nutrient intake throughout the day, that may improve glucose and insulin metabolism, appetite regulation (hunger and satiety); thus reducing risk of becoming overweight (5). Moreover, breakfast consumption may improve cognitive function and school performance (5). Thus, our findings are concerning due to the lower prevalence of regular breakfast consumption in athletes, as compared to young students from Brazil (34), who reported a frequency higher than 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O consumo alimentar inadequado durante a juventude é extremamente preocupante pois está relacionado a diversos fatores de risco para doenças cardiovasculares, como hipertensão, dislipidemia, hiperinsulinemia e resistência à insulina; além de comorbidades como diabetes mellitus tipo 2, síndrome do ovário policístico, entre outras anormalidades respiratórias, ortopédicas e hepáticas (REILLY et al, 2003). Crianças e adolescentes obesos também apresentam mais frequentemente distúrbios psicológicos (REILLY et al, 2003), baixo rendimento escolar (KIM et al, 2016), e anormalidades no ciclo menstrual (RUPA VANI et al, 2013). Além disso, a prevalência de distúrbios alimentares, como a compulsão alimentar, tem aumentado entre adolescentes (DAVIS, 2013).…”
Section: Lista De Figurasunclassified